HUBUNGAN ORIENTASI KEWIRAUSAHAAN DENGAN PERTUMBUHAN UMKM: PERAN ASPEK PERMODALAN DAN PEMERINTAH SEBAGAI MODERATOR - Shafariah, Hanuna; Edison, Edison; Mattajang, Rio (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2016)
This study aimed to examine the relationship between entrepreneurial orientation (EO) with of SMEs growth, and capital factors and government support as a moderator. Using the data collected from 90 SMEâ€™s, the study employs Hierarchical moderated regression analysis was used to test the hypotheses. The statistical results lead to the following conclusions: EO has a signiï¬cant positive relationship with SME's growth, but the role of capital factors and government support as moderator unsupported. The implication of these findings is that the government and financial institutions as the two institutions need to increase their role to encourage the growth of SMEs in terms of information provision, access to markets, capital, and training needs so it can serve as a reference for determining the development strategy of SMEs in the future. From the business owners or SMEs themselves, this research can be used as guidelines for business performance improvement through entrepreneurship-oriented behavior. Keywords: entrepreneurial orientation, SMEs growth